A microenvironment-determined risk continuum refines subtyping in meningioma and reveals determinants of machine learning-based tumor classification - Maas, Sybren L. N.; Tang, Yiheng; Stutheit-Zhao, Eric; Rahmanzade, Ramin; Blume, Christina; Hielscher, Thomas; Zettl, Ferdinand; Benfatto, Salvatore; Calafato, Domenico; Sill, Martin; Benotmane, Jasim Kada; Yabo, Yahaya A.; et al. (Nature genetics, 2026)
Classification of tumors in neuro-oncology today relies on molecular patterns (mostly DNA methylation) and their machine learning-supported interpretation. Understanding the process of algorithmic interpretation is essential for safe application in clinical routine. This is paradigmatically true for the most common primary intracranial tumor in adults, meningioma. Here, by applying multiomic profiling and multiple lines of orthogonal computational evaluation in multiple independent datasets, we found that not only tumor cell characteristics but also incremental changes in the tumor microenvironment (TME) have impact on epigenetic meningioma classification and clinical outcome. Besides revealing the decisive role of non-neoplastic cells in the CNS methylation classifier, this challenges the model of distinct meningioma subgroups toward a TME-determined risk continuum. This refines current controversies in molecular meningioma subtyping. In addition, we apply these learnings to devise and validate a simple diagnostic approach for increased clinical prediction accuracy based on immunohistochemistry, which is also applicable in resource-limited settings.
Online veröffentlicht: 9. Februar 2026
Gesehen am 02.03.2026